2019
DOI: 10.3390/fermentation5010021
|View full text |Cite
|
Sign up to set email alerts
|

Direct Ethanol Production from Lignocellulosic Materials by Mixed Culture of Wood Rot Fungi Schizophyllum commune, Bjerkandera adusta, and Fomitopsis palustris

Abstract: The cost of bioethanol production from lignocellulosic materials is relatively high because the additional processes of delignification and saccharification are required. Consolidated bioprocessing (CBP) simultaneously uses the multiple processes of delignification, saccharification, and fermentation in a single reactor and has the potential to solve the problem of cost. Some wood-degrading basidiomycetes have lignin- and cellulose-degrading abilities as well as ethanol fermentation ability. The white rot fung… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…It has the capability of converting xylan directly to ethanol. Horisawa et al (2019) suggested direct ethanol production from lignocellulosic materials by consolidated bioprocessing using the mixed culture of wood rot fungi, i.e., Schizophyllum commune, Bjerkandera adusta, and Fomitopsis palustris.…”
Section: Xylanase Employed In Biorefinerymentioning
confidence: 99%
“…It has the capability of converting xylan directly to ethanol. Horisawa et al (2019) suggested direct ethanol production from lignocellulosic materials by consolidated bioprocessing using the mixed culture of wood rot fungi, i.e., Schizophyllum commune, Bjerkandera adusta, and Fomitopsis palustris.…”
Section: Xylanase Employed In Biorefinerymentioning
confidence: 99%
“…It is thus likely that these organisms temporarily tolerate microaerophilic to anaerobic growth environments by switching to fermentative metabolism while they decompose wood. In fungi, production of ethanol by sugar fermentation is apparently a conserved trait that is not restricted to only the Ascomycota yeasts like Saccharomyces cerevisiae [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Ethanol is the second important metabolite produced by fungi (e.g., A. nidulans , A. fumigatus , S. cerevisiae ) as an alternative electron acceptor to recycle NAD(P) + under anaerobic conditions (Shimizu et al ., 2010; Grahl et al ., 2011; Horisawa et al ., 2019). RNA‐seq analysis also demonstrated that fungi produce ethanol by up‐regulating the genes involved in glycolysis in response to a low level of molecular oxygen (Setiadi et al ., 2006; Askew et al ., 2009; Masuo et al ., 2010).…”
Section: Discussionmentioning
confidence: 99%